Evaluación de densidades de trampeo y dosis del atrayente alimenticio cera trap para el control de la mosca de la fruta (Ceratitis capitata) en el cultivo de mandarina (Citrus reticulata), cantón Patate, provincia Tungurahua. - Pilco Quispe, Christian Andrés (2021)
The fruit fly Ceratitis capitata is an insect of the family (Tephritidae) considered a pest of major importance worldwide. It causes damage to mandarin fruit, destroying its pulp, reducing its quality and therefore restricting it to the national and international markets. This research was carried out in the community of San Javier, Patate canton, province of Tungurahua at an altitude of 1995 meters above sea level. The objectives of the research were: i) To identify the density of trapping per hectare that helps to capture more fruit flies. ii) To know the dose of the food attractant Cera Trap that has a higher capture of fruit flies. iii) To determine the population dynamics of Ceratitis capitata during the research. iv) To identify the genus of fruit flies captured in the traps. The treatments were two trapping densities and two doses of the food attractant Cera trap. The fruit fly was checked and counted every 14 days during the 56 days of the research. Analysis of variance, Tukey's test at 5% and a correlation and regression analysis were performed. No significant statistical differences were found in each treatment; however, it was observed that T2 (30 traps/ha with 300 cc of Cera trap) was more efficient in capturing fruit flies than the other treatments, with a ratio of females to males of 6.39:1. The fruit fly population dynamics at 14, 28, 42 and 56 days are 0.043, 0.215, 0.245 and 0.16 MTD (trap fly day).